2019
DOI: 10.1002/jcc.26008
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Signatures of Hydroxyl‐ and Water‐Terminated Neutral and Tetra‐Anionic Mn12‐Acetate

Abstract: We investigate the energetics and magnetic signatures of the parent molecular magnet Mn12‐Acetate [Mn12O12(COOR)16(H2O)4] and a chemically decomposed version of this structure, in which the four water molecules are converted to hydroxyl groups and hydrogen molecules. We determine electron addition and water decomposition energetics for this water‐containing molecule using density‐functional methods and include the recent Fermi‐Löwdin‐Orbital self‐interaction correction. We find that it only costs 0.32 eV to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
(172 reference statements)
0
6
0
Order By: Relevance
“…In practical FLOSIC calculations, optimal FOD positions are found using gradients of the energy with respect to FOD positions, in a procedure analogous to molecular geometry optimizations [25,26]. A number of studies have been conducted using the FLOSIC method [24,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In practical FLOSIC calculations, optimal FOD positions are found using gradients of the energy with respect to FOD positions, in a procedure analogous to molecular geometry optimizations [25,26]. A number of studies have been conducted using the FLOSIC method [24,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…They present some of the most complicated multireference quantum chemistry problems in the biological world. Combined theoretical and experimental studies, primarily at the level of density functional theory, have proven successful in unravelling many structural and electronic features of such enzyme active sites [27][28][29]. However, a detailed understanding of the interplay between spin-coupling and delocalization between metals, which requires true multi-reference quantum chemistry and is needed to interpret aspects of experimental spectroscopy, remains in its infancy [23,24,[30][31][32].…”
Section: A Quantum Chemistrymentioning
confidence: 99%
“…The computational effort in the FLOSIC method allows for its application to clusters that were inaccessible through previous implementations 37,38 of PZ SIC. The FLOSIC methodology has been used to study properties of chemical and physical interest for a range of systems [39][40][41][42][43][44][45][46][47][48] including water 2,[49][50][51] . It has been shown that PZ SIC applied with SCAN significantly reduces the overbinding of HBs in neutral water clusters, predicting binding energies in much closer agreement with the CCSD(T)-F12, and simultaneously retaining the correct energetic ordering among the water hexamer isomers 2 .…”
Section: Introductionmentioning
confidence: 99%